Treatment and survival analysis for 40-year SEER data on upper esophageal cancer - Wu, Xi; Zhu, Ming-Chuang; Li, Guo-Liang; Xiong, Peng; Sun, Wei; Zhang, Ni; Zhao, Bo; Li, Le-Qun; Fu, Xiang-Ning; Zhu, Min (Frontiers in Medicine, 2023)
Background: Upper esophageal cancer (UEC) is rare in both eastern and western countries. The epidemiological characteristics and long-term survival of UEC patients are less known. In addition, the choice of optimal treatment for UEC has been controversial. Methods: Cases of UEC (C15.3 and C15.0) arising during the period from 1973 to 2013 were identified and selected using the SEER database. Student’s t test and Pearson’s chi-square test were used to compare the differences in parameters among different groups. Esophageal cancer-specific survival (ECSS) and overall survival (OS) rate were calculated by Kaplan–Meier method. Cox proportional hazard regression was used to analyze predictive factors. Results: In the past 40 years, the cases of UEC has gradually increased, and the proportion of adenocarcinoma (AD) has gradually increased (from 3.6% to 11.8%, p < 0.001). There has been a significant increase (1973-1982 vs. 2004-2013) in median OS (7 months vs. 10 months, p<0.001) and median ECSS (7 months vs. 11months, p < 0.001) among UEC patients from 1973 to 2013. For the impact of different treatments, the results showed that the ECSS and OS of surgery without radiation (SWR) and radiation plus surgery (R+S) were superior to those of radiation without surgery (RWS). Subgroup analysis showed that ECSS and OS were highest among patients treated with SWR, compared with R+S and RWS for patients with localized disease. For regional disease, ECSS and OS were highest among patients with R+S, compared with SWR or RWS. Among patients with regional-stage squamous cell carcinoma (SCC), OS was higher with neoadjuvant radiotherapy or adjuvant radiotherapy, compared with SWR. Multivariate analysis showed that radiotherapy sequence was dependently associated with OS among patients with regional-stage SCC. Conclusion: Although, the long-term survival of UEC remains poor, it has gradually increased since 1973. This should be closely related to the improvement of medical care over the past 40 years. Different treatment methods have great influence on the long-term survival of UEC. For localized disease, surgery may be a better choice. For regional disease, surgery plus adjuvant or neoadjuvant radiotherapy may be more beneficial to improve the long-term prognosis of UEC patients.